Profitabilitas, Ukuran Perusahaan, Dan Struktur Modal Terhadap Nilai Perusahaan F&B - Aulia Citra; Hilda Mary; Mardhatila Fitri Sopali (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the influence of profitability and company size on company value with capital structure as an intervening variable in Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023 a total of 95 companies. The population of this study is all Food and Beverages companies listed on the Indonesia Stock Exchange in 2019-2023. Until a sample of 30 samples from the criteria that have been determined. The method used in this study is a survey method of quantitative descriptive approach. The technique used is the purposive sampling technique. The data analysis used in this study is multiple linear regression analysis by using the SPSS 25 test tool. The results of the study show that profitability and company size have a significant effect on the capital structure. Profitability and capital structure have a significant effect on the value of the company, while the size of the company has no effect on the value of the company. Capital structure is not able to mediate the influence of profitability and company size on company value in Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The source of this data research is carried out from annual reports and financial statements obtained from www.idx.co.id